Systemic Granulomatous Pathology in Two Captive Alligator Mississippiensis - Rizac Raluca Ioana (Sciendo, 2019)
The literature in this field cites various ubiquitous fungal and bacterial microorganisms as etiologic agents in severely stressed captive alligators and crocodiles. This study reports two cases of Alligator mississippiensis with bacterial and fungal disease. Two adult American alligators have been submitted for post-mortem investigations. Necropsy, cytology (MGG), and histopathology investigations (HE, HEA, PAS, Gram, Giemsa, Ziehl Neelsen) were carried out. Pleural and pericardial swabs were subjected to microbiological examination. The main lesions detected involved the lower respiratory system and were characterized by thoracic serosanguineous effusions, pleural and pulmonary nodules (1 – 80 mm), accompanied by edema. Similar nodules observed also in the liver, spleen and myocardium, suggested a systemic disease. Additionally, cutaneous, gingival and gastrointestinal erosions and ulcers were found. Cytoarchitecture findings in the major organs revealed lymphoid depletion, multifocal to coalescing necrotic areas with coccoid aggregates and rod shaped bacteria intermixing fungal structures, boarded by heterogeneous inflammatory infiltrates, composed by epithelioid macrophages, lymphocytes and heterophils. The microbiological examination revealed the presence of Aeromonas hydrophila, A. caviae, Serratia marcescens, Pantoea agglomerans, Proteus vulgaris, haemolitic and non-haemolitic E. coli, Citrobacter freundii, Rhizopus/Absidia from pleural and pericardial cavities, concluding that death occurred following a bacterial and fungal pneumonia, with secondary spreading of microorganisms. Along with the low immune response, severe stress was the main possible cause, as a result of environmental temperature changes during the winter, as well as other husbandry issues.